Ecological threats of local communities: Losses in the Pomeranian Voivodeship, after the storm of 11th/12th August 2017 - Wodzikowski, Czesław (Studia Ecologiae et Bioethicae, 2019)
The article presents the effects of the storm of 11th/12th August 2017 in the context of ecological threats to local communities in the affected area in the Pomeranian Voivodeship. The estimated valuation of material losses presented in the article is divided into several categories: losses in forests, network infrastructure, agriculture, residential buildings, public property and companies. The author also refers to the issues of ecosystem services and environmental resilience in the aspect of ecological security and of sustainable development from the perspective of the quality of life of local communities. It has been hypothesised that ecological security on a local scale depends on the condition of the main types of ecosystems occurring in the analysed area – in this case, forests, and especially services generated by these ecosystems.